The Feed Conversion Ratio and Feed Digestibility of Feed Substituted with Azolla microphylla Meal for Tilapia Fry - Herlina , Herlina; Mulyani, Sri; Budi, Sutia (Agrikan Jurnal Agribisnis Perikanan, 2025)
The high cost of commercial fish feed and the limited availability of highly nutritious, cost-effective, and environmentally friendly feed ingredients pose challenges in producing high-quality tilapia fingerlings (Oreochromis niloticus). The efficiency of nutrient absorption in fish digestion and growth performance is generally evaluated through the feed conversion ratio (FCR) and digestibility values. This study aimed to determine the effect of substituting commercial feed with fermented Azolla microphyll meal on the proximate composition and digestibility of tilapia fingerlings. The study was conducted from June to July 2024 at the Tanabangka Village Fish Hatchery Unit, Bajeng Barat District, Gowa Regency, and at the Brackishwater Preliminary Aquaculture Research Laboratory in Maros. The research employed a completely randomized design with four treatments and three replicates. The treatment groups were as follows: A) 100% commercial feed as control, B) 25% commercial feed and 75% Azolla meal, C) 50% commercial feed and 50% fermented Azolla microphyll meal, and D) 75% commercial feed and 25% fermented Azolla microphylla meal. The results showed that fermented Azolla microphyll meal can serve as a viable alternative to commercial feed. A feed composition of 50% commercial feed and 50% fermented Azolla microphylla meal yielded an FCR of 1.37±0.05. Meanwhile, combining 75% commercial feed with 25% fermented Azolla microphyll meal produced total and protein digestibility values of 84.51±0.78% and 92.47±0.59%, respectively. These findings suggest that integrating fermented Azolla microphylla into feed formulations can enhance nutrient utilization efficiency and reduce dependence on commercial feed in tilapia aquaculture.